Influence of chamber pressure on CNG jet characteristics of a multi-hole high pressure injector. (1st June 2017) - Erfan, Iman; Hajialimohammadi, Alireza; Chitsaz, Iman; Ziabasharhagh, Masoud; Martinuzzi, Robert J.
Abstract: Natural Gas Direct Injection (NGDI) engines have attracted attention of engine manufacturers because of low pollutant emissions and high efficiency. The jet structure and injector properties are control parameters for optimal mixture formation and stable combustion. Here, the jet characteristics are investigated experimentally. The natural gas jet, injected through a multi-hole injector, is visualized using Schlieren photography. The effects of injection and chamber pressures on macroscopic jet characteristics are examined. New correlations for tip speed and tip penetration are presented. Results show that reducing chamber pressure is more effective than injection pressure for increasing the jet axial penetration. Moreover, the linear relation between non-dimensional tip penetration and time is dependent on the chamber-to-injected gas density ratio.